Context Awareness Technology Using Parallel Mining for Ambient Assisted Living System - Vivek, J; Maharnisha, Gandla; Roopesh Kumar, Gandla; Karun Sagar, Ch; Arunraj, R (International Journal of Engineering and Technology, 2018)
In this paper, context awareness is a promising technology that provides health care services and a niche area of big data paradigm. The drift in Knowledge Discovery from Data refers to a set of activities designed to refine and extract new knowledge from complex datasets. The proposed model facilitates a parallel mining of frequent item sets for Ambient Assisted Living (AAL) System [a.k.a. Health Care [System] of big data that reside inside a cloud environment. We extend a knowledge discovery framework for processing and classifying the abnormal conditions of patients having fluctuations in Blood Pressure (BP) and Heart Rate(HR) and storing this data sets called Big data into Cloud to access from anywhere when needed. This accessed data is used to compare the new data with it, which helps to know the patients health condition.